NON-GENETIC FACTORS THAT PREPARATED PENEUMONIA INCIDENCE IN HOLSTEIN CATTLE AND THEIR EFFECT ON MILK-PRODUCTION IN THE MIDDLE OF IRAQ - Garabed A. Baghdasar (Mesopotamia Journal of Agriculture)
Statistically analyzed 5226 records for factors preparated pneumonia incidence which were parity , year and season of incidence with 2046 records refer to total milk production (TMP) and location period (LP) were collected during 1998 to 2001 on Holstein cows at Al-Nasr Dairy Cattle Station near to Al-Soueria . The over all mean for the % of pneumonia among cows was 10.73% and affected high significantly by parity, year and season. The over all mean ± SE for TMP was 4198.75 ± 24.45 kg which significantly (p <0.01) affected by parity , incidence and lactation ion period , while it was (p<0.05) for year and season of incidence. The TMP for healthy cows was 4348.11 ± 84.99 kg while the production reduced to 4163.39 ± 84 kg in those infected cows. The over all mean ± SE for LP was 326.74 ± 1.72 days and this was affected highly significantly by parity , year and case of disease but did not affected by season of incidence so as a shorter LP for infected cows was 313.77 ± 6.56 day and increased to 324.67 ± 5.98 days in healthy cows . So, we need to do more studies for this disease and do a genetic evaluation for higher resistance cows.